Executive Committee Minutes 2009-02-26 - Academic Senate:::::::::
Approval of faculty governance assigned time '09 – '10, Revision to Policy on Representation on Administrative Search Committees, Definition of Faculty in Senate Constitution, Senate Block in Newsbytes